Oral squamous cell carcinoma – do we always need elective neck dissection? evaluation of clinicopathological factors of greatest prognostic significance: a cross-sectional observational study - Michcik, Adam; Polcyn, Adam; Sikora, Maciej; Wach, Tomasz; Garbacewicz, Łukasz; Drogoszewska, Barbara (Frontiers in Oncology, 2023)
The aim of the study was to find clinical and pathological factors with the greatest prognostic significance in patients with OSCC. The analysis included 125 patients grouped according to the tumor primary site (TPS): the floor of the mouth (FOM), tongue (TC) and retromolar triangle (RMT). Grading (G), tumor size (pT), nodal metastases (NM), local recurrence (LR), nodal recurrence (NR), perineural invasion (PNI), lymphovascular invasion (LVI), extranodal extension (pENE), and nodal yield (NY) were evaluated in each group. Results: With regard to TPS, FOM appeared to be the most metastatic. However, the recurrence rate was similar to TC tumors, which were characterized by higher G than those in other locations. When analyzing G, the highest percentage of LR (40.5%) and NM (34.5%) was observed among patients with G2. As G increased, so did the number of pENE G1 – 7.4%; G2 – 31%; G3 – 35.7%; LVI: G1 – 25.9%; G2 – 50%; G3 – 57.1%; PNI: G1 – 29.6%; G2 – 47.6%; G3 – 92.9%; NR G1 – 14.8%; G2 – 32.1%; G3 – 21.4%. Grading did not affect the type of growth and did not directly affect the occurrence of NR. pT and DOI increased the frequency of NM but we did not observe any effect of pT and DOI on LR, PNI, and LVI. NY in the study group did not increase the risk of NR. Conclusion: Tumor primary sites within the FOM, TC, and pT classification are the factors that increase the risk of NM and LR. However, apart from the primary site predisposing to the occurrence of NM, the histological structure of the tumor turned out to be the most important feature affecting the patient's prognosis. The number of cases of pENE+, LVI+, PNI+, NM+, and NR+ increased with the increase in G. Although the pT, DOI increased the frequency of NM, we did not observe the effect of the pT and DOI on LR, PNI and LVI. Thus, even in the case of a small tumor of the FOM and TC with at least G2, elective neck dissection should be performed each time.